Value chain surveys: What do they cover, and how well? - Ambler, Kate; de Brauw, Alan; Herskowitz, Sylvan; Pulido, Cristhian (International Food Policy Research Institute, 2022)
While agricultural value chains are rapidly evolving (Reardon, 2015; Reardon et al., 2021; Barrett et al., 2022), research attention has increasingly taken notice of the important role played by actors in the ag ricultural midstream. The agricultural midstream consists of activities that take place after production but before final sale to consumers, with existing literature highlighting transportation, trading/wholesaling, processing/packaging, and storage as key activities (Reardon, 2015; Ambler et al., 2022a). However, even as research on the agricultural midstream has been growing, little is known about the poten tial financial needs or capabilities of midstream actors (Ambler et al., 2022a; Bellemare et al., 2021; Reardon and Minten, 2021). If midstream actors face meaningful financial constraints in growing their businesses, it can hinder employment opportunities, increase consumer food prices, depress agricul tural producer prices, or constrain growth more broadly.